Myocardial Viability Multimodality Visualization: Ukrainian Cardiovascular Surgeons Association Expert Consensus Guidelines - Lazoryshynets, Vasyl V.; Rudenko, Anatoliy V.; Fedkiv, Svitlana V.; Potashev, Sergiy V.; Salo, Sergii V.; Mazur, Oleksandra A. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Myocardial loss due to necrosis in coronary artery disease (CAD) remains the main cause of heart failure. In these circumstances myocardial mass loss severity identification by cardiac visualization and, conversely, myocardial visualization evaluation are useful from the clinical point of view for decision making and therapeutical strategy choice in patients with left ventricular ischemic dysfunction. Myocardial viability in clinical practice is defined as myocardium in acute or chronic CAD or other myocardial pathology with contractile dysfunction with preserved electric function and metabolism with potential to restore myocardial function after revascularization or other interventions. There is a number of pathophysiological conditions explaining viability and often coexisting. Visualization in cardiology and cardiac surgery allows myocardial viability identification using different methodologies and principles in order to predict potential myocardium response to treatment and optimal therapeutic strategy choice. The aim of these Guidelines is to provide comprehensive and critical review of contemporary indications and methods of myocardial viability evaluation as well as to describe state of art standards for these techniques and multimodality visualization results interpretation, including clinical scenarios where it could be useful. This paper is based on an expert consensus document from the European Association of Cardiovascular Imaging (EACVI) (2021) and reviews up-to-date data about viable myocardium pathophysiology and its assessment visualization methods, particularly, modern imaging techniques including stress echocardiography with B-mode speckle tracking (STE), single photon emission computed tomography (SPECT), positron emission tomography (PET) cardiovascular magnetic resonance imaging (cardiac MRI) and multisliced computed tomography (MSCT). It also provides clinical guidelines for these imaging methods acquisition, interpretation and standardization. The most widespread clinical scenarios, where myocardial viability assessment would be useful, are presented.